2005
DOI: 10.1021/es050231b
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of 226Ra2+ from Gas-Field-Produced Waters

Abstract: The 226Ra2+ selectivity of both the self-assembled (iso)-guanosine-based systems and ionizable thiacalix[4]crown dicarboxylic acids was determined in gas-field-produced water and a metal ion-containing model solution (simulant). Seven gas-field-produced water samples have been analyzed. From a sample (K5D) with average metal ion concentrations ([metal(tot)] = 0.14 M), thiacalix[4]crown-5 dicarboxylic acid (10(-4) M) extracts 60% of the 226Ra2+ content. Extractions performed with the model solution ((M)K5D) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…29 A further body of work in this eld has been directed towards the development of organicsoluble extractants that partition this ion to the organic phase in biphasic systems. [29][30][31][32][33][34][35][36][37][38] Of these extractants, the most common structural motif explored has been that containing a calixarene core. Although calixarene-based ligands have demonstrated efficiency for the selective extraction of Ra 2+ in the context of environmental remediation, [32][33][34][35] attempts to use these ligands for Ra 2+ complexation for nuclear medicine applications have been unsuccessful due to either failed radiolabeling 36 or poor kinetic stability of the resulting complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A further body of work in this eld has been directed towards the development of organicsoluble extractants that partition this ion to the organic phase in biphasic systems. [29][30][31][32][33][34][35][36][37][38] Of these extractants, the most common structural motif explored has been that containing a calixarene core. Although calixarene-based ligands have demonstrated efficiency for the selective extraction of Ra 2+ in the context of environmental remediation, [32][33][34][35] attempts to use these ligands for Ra 2+ complexation for nuclear medicine applications have been unsuccessful due to either failed radiolabeling 36 or poor kinetic stability of the resulting complex.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] Of these extractants, the most common structural motif explored has been that containing a calixarene core. Although calixarene-based ligands have demonstrated efficiency for the selective extraction of Ra 2+ in the context of environmental remediation, [32][33][34][35] attempts to use these ligands for Ra 2+ complexation for nuclear medicine applications have been unsuccessful due to either failed radiolabeling 36 or poor kinetic stability of the resulting complex. 29 These unsuccessful efforts have led many in the radiopharmaceutical community to the conclusion that stable chelation of 223 Ra sufficient for its in vivo use cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the [1 + 1] coupling between the corresponding bis(mercaptomethyl)-8 and bis(bromomethyl)-naphthalenes 9, respectively, in basic and high dilution conditions produced tetrahomodithiacalix [4]naphthalenes 10 and 11 12,13 in reasonable yields (Scheme 2). These new homodithiacalix [4]naphthalenes were used as precursors for the syntheses of the corresponding homocalix [4]naphthalenes via extrusion of the sulfur atoms, 11 and although these compounds were found to be able to complex with Ag + their complexation properties were not investigated in any detail at that time.…”
Section: Resultsmentioning
confidence: 99%
“…Ag + , Zn 2+ , Cd 2+ , Hg 2+ ), alkali or alkaline earth metal ions, 3 and as has recently been shown, for the selective removal of 226 Ra from gas-field-produced waters. 4 Thiacalix [4]arene itself has been prepared using either a one-step procedure, 5 from para-tert-butylphenol and sulfur, or more efficiently via the sulfur-bridged dimer 2, 6 or by a less efficient multi-step process via the linear tetramer 3 7 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a signicant radium ion ( 226 Ra 2+ ) preference over other monovalent alkali cations was observed for both 57 and 53, with a "precipitation prevention/ dissolving" property over a wide pH range. And, in 2005, Reinhoudt 193 et al reported that Ra 2+ can be selectively extracted from gas-eld produced water by isoG-based self-assemblies.…”
Section: Numbermentioning
confidence: 99%